2001
DOI: 10.1128/aac.45.9.2616-2622.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Fluorescence Assay for Human Immunodeficiency Virus Type 1 Protease Activity

Abstract: The human immunodeficiency virus type 1 (HIV-1) protease is essential for production of infectious virus and is therefore a major target for the development of drugs against AIDS. Cellular proteins are also cleaved by the protease, which explains its cytotoxic activity and the consequent failure to establish convenient cell-based protease assays. We have exploited this toxicity to develop a new protease assay that relies on transient expression of an artificial protease precursor harboring the green fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Because the expression of HIV-1 PR has been associated to apoptosis and cell cycle when expressed (Strack et al, 1996;Wallin et al, 1990;Shoeman et al, 1990), cell cycle and apoptosis Annexin 5 analyses were performed using FACS. These analyses did not reveal any effects of PR expression on cell cycle or apoptosis levels using the transient conditions described in the assays shown here perhaps because the PR is expressed from a precursor protein, a context which has already been shown to prevent the cytotoxicity of HIV-1 PR (Lindsten et al, 2001 and data not shown).…”
Section: Effects Of Gag/pol Expression On Apoptosis and Cell Cyclementioning
confidence: 65%
“…Because the expression of HIV-1 PR has been associated to apoptosis and cell cycle when expressed (Strack et al, 1996;Wallin et al, 1990;Shoeman et al, 1990), cell cycle and apoptosis Annexin 5 analyses were performed using FACS. These analyses did not reveal any effects of PR expression on cell cycle or apoptosis levels using the transient conditions described in the assays shown here perhaps because the PR is expressed from a precursor protein, a context which has already been shown to prevent the cytotoxicity of HIV-1 PR (Lindsten et al, 2001 and data not shown).…”
Section: Effects Of Gag/pol Expression On Apoptosis and Cell Cyclementioning
confidence: 65%
“…In particular, the human immunodeficiency virus protease is a major target for therapeutic strategies to treat AIDS. However, given the continual emergence of inhibitor-resistant strains, a diagnostic strategy was devised to monitor treatment efficacy and progression of viral infection, based on a genetically encoded GFP-protease precursor of HIV-1 [171,172].…”
Section: Sensors Of Signal Transduction Pathwaysmentioning
confidence: 99%
“…Previously, we reported a new PR assay based on transient expression of an artificial PR precursor harboring the green fluorescent protein (GFP-PR) (Lindsten et al, 2001). The precursor is activated in vivo by HIV PR autocatalytic cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with therapeutic doses of PIs results in a dose-dependent accumulation of the fluorescent precursor in transiently transfected cells that can be easily detected and quantified. This provides a convenient and non-infectious model for high-throughput screenings of substances that can interfere with the activity of the PR in living cells (Lindsten et al, 2001).…”
Section: Introductionmentioning
confidence: 99%